Exploring undergraduate medical students and faculty perspectives on blended learning: a qualitative study in China - Xi Chen; Lei Zhou; Lin Lv; Chunhui Zhang; Xi Yu; Sisi Li; Xunchen Liao; Shaoyu Wu (BMJ Open)
Objectives This study aimed to explore the views and expectations of medical students and faculty members on blended learning following university-wide teaching reforms, focusing on its influence on self-directed learning (SDL) and educational effectiveness.Design A qualitative study employing grounded theory methodology with semistructured individual and group interviews.Setting A tertiary medical university after institution-wide educational reforms.Participants One administrator, 11 faculty members and 30 third-year preclinical medical students were recruited to participate in the study.Results The analysis of faculty and student perceptions yielded two core categories from faculty and three from students. Faculty highlighted the comparison between face-to-face and online instruction, emphasising the influence of students’ learning attitudes, SDL abilities, teachers' beliefs and teaching strategies on blended learning outcomes. Students shared their learning preferences and challenges with SDL, identifying learning attitudes, teaching management and learning methods as key factors impacting blended learning success.Conclusions The study highlights that teachers’ positive beliefs enhance blended learning success, while fostering students’ self-directed skills and learning attitudes, along with addressing challenges and needs, is key to effective strategies.